Freeman-Sheldon Syndrome: A Case Report - Salehpour MD, MPH, SH.; Saket MD, S. (Iranian Journal of Child Neurology, 2009)
Objective The Freeman-Sheldon syndrome is a rare congenital myopathy and dysplasia, in which fibrotic contractures of the facial muscles result in the characteristic "whistling face". Difficulties with intubation may be attributed in part to microstomia and micrognathia. In addition to other deformities, limb myopathy results in ulnar flexion contractures of the hand and equinovarus/valgus deformities of the feet. Intravenous access may be difficult because of limb deformities and thickened subcutaneous tissues. Limbs may be encased in plaster casts or splints limiting the available sites for venepuncture. The authors report with a review of literature the case of an infant with Freeman-Sheldon syndrome, which his characteristics was mentioned above.